Effectiveness of Treffinger Model Implementation to Improving Mathematics Learning Outcomes - Eka Putra Utama; I Ketut Sudarsana (Jayapangus Press, 2023)
The mathematics learning outcomes of class VII have not yet reached the Minimum Completeness Criteria (KKM) set. Learning activities have not activated students because learning is still carried out in one direction. The purpose of this study was for the pretest and post-test results of students after using the treffinger model in learning mathematics and to determine the effectiveness of the treffinger model in learning mathematics in students. The research approach used is quantitative with the type of pseudo experiment and without control. The research variables used are the treffinger model as the independent variable and mathematics learning outcomes as the dependent variable, with a population of VII grade students of SMPN 2 Enrekang in the 2018/2019 school year consisting of 4 classes, namely VIIA, VIIB, VIIC, and VIID classes so that the sample used is VIIB class with cluster random sampling technique. The data obtained were analyzed with descriptive statistics and inferential statistics. Descriptive statistics were carried out by looking at the analysis of learning outcomes with an increase in the average score from the pretest results of 46.2 to 77.4 on the posttest results, the average student activity of 88.75%, the average teacher's ability to manage the class with a score of 4.4 or with a very good category and the average student response to learning of 88%. Inferential statistics conducted with a one-sample t-test showed a significance value below α = 0.05 so that H1 was accepted. From these data, it can be concluded that the application of treffinger learning model in class VII students of SMPN 2 Enrekang is effective.